Formulasi Sabun Mandi Cair Berbasis Virgin Coconut Oil (VCO): Optimalisasi Pemanfaatan Produk Lokal Untuk Perawatan Kulit dan Pencegahan Dehidrasi - Maulina, Novia; Muslikh, Faisal Akhmal; Nastiti, Ginanjar Putri; Fadilla, Rahma Nur; Winayah, Mesri Ananta; Kamelin, Badira; Firdaus, Natasya Octavia Putri; Fricananta, Salma Salsabila; Dewi, Tanaya Jati Dharma (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2025)
Skin dehydration is a common issue affecting 40–50% of the adult population, resulting in dry, rough, and dull skin, as well as itching, irritation, and premature aging. The